Some Trends in EAEU Cooperation with Latin-Caribbean America - A. V. Toropygin; A. V. Nikolaenko (Евразийская интеграция: экономика, право, политика)
The Eurasian Economic Union (EAEU) is a rapidly developing integration structure. Its main priority in activities is economic development, even more precisely, trade. At the same time, at the beginning of its activities, the main attention of the member states of the association was focused on the development of domestic trade. The creation of a customs union and a single economic space basically solved this problem. The current development of the structure, in accordance with the global trend, was the expansion of trade relations with border, regional and non-regional partners. Thus, there is a process of integration of integrations, i.e. interaction at the level of integration structures and individual states. Since the EAEU’s main activity is the economy, first of all, we are talking about the creation of Free Trade Zones (FTAs).Aim. The purpose of the article is to identify the dynamics and directions of the development of relations between the EAEU and the countries of Latin America and the Caribbean.Tasks. Consider the main trends and stages of interaction between the LACB countries and the EAEU; identify new directions for the development of Eurasian integration.Methods. The use of a systematic approach made it possible to analyze integration processes taking into account various directions. The method of historical and comparative analysis was used to compare the concepts of the development of integration. Situational analysis made it possible to demonstrate the dynamics of the development of Eurasian integration and the formation of interaction with external actors.The sociological approach made it possible to consider as a special variety of international structures with the characteristics of both intergovernmental bodies and organizations.Results. Against the background of the development of economic interaction, new areas of interaction have been identified.Conclusions. In the current third stage of cooperation between the EAEU and the LKA, the element of political communication of the organization’s information function is strengthened, which is a response to the political crisis on the one hand, and on the other, opposition to Western sanctions in terms of attempts to isolate Russia in the world.